[18F]AV‐1451 tau positron emission tomography in progressive supranuclear palsy. Issue 1 (27th October 2016) - Whitwell, Jennifer L.; Lowe, Val J.; Tosakulwong, Nirubol; Weigand, Stephen D.; Senjem, Matthew L.; Schwarz, Christopher G.; Spychalla, Anthony J.; Petersen, Ronald C.; Jack, Clifford R.; Josephs, Keith A.
ABSTRACT: Background: The [ 18 F]AV‐1451 positron emission tomography ligand allows the in vivo assessment of tau proteins in the brain. It shows strong binding in Alzheimer's dementia, but little is known about how it performs in progressive supranuclear palsy, a primary 4R tauopathy. Objectives: The objectives of this study were to determine whether [ 18 F]AV‐1451 uptake can be observed in progressive supranuclear palsy and to characterize the regional distribution when compared with controls and Alzheimer's dementia. Methods: [ 18 F]AV‐1451 positron emission tomography was performed in 10 patients with probable progressive supranuclear palsy. These patients were age‐ and gender‐matched to 50 controls and 10 Alzheimer's dementia patients who had undergone identical [ 18 F]AV‐1451 imaging. Regional comparisons of [ 18 F]AV‐1451 uptake were performed across the whole brain using region‐of‐interest and voxel‐level analyses, and correlations between regional [ 18 F]AV‐1451 and the progressive supranuclear palsy rating scale were assessed. Results: An elevated [ 18 F]AV‐1451 signal was observed in progressive supranuclear palsy when compared with controls in the pallidum, midbrain, dentate nucleus of the cerebellum, thalamus, caudate nucleus, and frontal regions. Signal in the cerebellar dentate and pallidum were also greater in progressive supranuclear palsy when compared with Alzheimer's dementia. Conversely, the [ 18 F]AV‐1451 signal across the cortex was higher in Alzheimer's dementia when compared with progressive supranuclear palsy. The [ 18 F]AV‐1451 signal in a number of regions correlated with the progressive supranuclear palsy rating scale. Conclusions: Progressive supranuclear palsy is associated with an elevated [ 18 F]AV‐1451 signal in a characteristic and distinct regional pattern that correlates with disease severity and differs from the patterns observed in Alzheimer's dementia. © 2016 International Parkinson and Movement Disorder Society.